180k views
5 votes
.......................

.......................-example-1

2 Answers

2 votes


(5x + 50)/(x+5) \ \ \centerdot \ \ (1)/(x +10 )


= (5(x + 10))/(x+5) \ \ \centerdot \ \ (1)/(x +10 )


= (5)/(x+5)

-


\bold {\text {Answer : }(5)/(x+5)}

User Dyaa
by
5.5k points
4 votes

First factor 5x + 50

5x + 50 = 5(x + 10)

(5(x + 10))/(x + 5) x (1)/(x + 10)

Simplify. Note that there is a x + 10 in both numerator and denominator. Cancel them out

(5(x + 10))/(x + 5) x 1/(x + 10)

5/(x + 5) x 1/1

Simplify.

5 x 1 = 5

(x + 5) x 1 = x + 5

5/(x + 5) or (B) is your answer

hope this helps

User Alex  Glinsky
by
6.0k points